Perbandingan Peramalan Penjualan Oil Filter di PT. United Tractors Surabaya dengan Metode Autoregressive Integrated Moving Average (ARIMA), Exponential Smoothing (ES), Trend Moment - Kirana Enggar Kusuma; Farizi Rachman; Aditya Maharani (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
PT. United Tractors is a heavy equipment distribution company selling spare parts such as oil filters. The results of the problems being faced by PT. UT cannot meet customers' demand; therefore, an oil filter sales forecasting analysis uses the Autoregressive Integrated Moving Average (ARIMA), Exponential Smoothing (ES), and Trend Moment method. The results of calculations and research carried out after processing data from 2013 to 2022, the slightest error value is obtained in the Exponential Smoothing method with the Double Exponential Smoothing model using a= 0.9. The accuracy values obtained are MAD= 5.021, MSE= 59.674, dan MAPE= 0.086%, when compared to ARIMA, MAD= 8.192, MSE= 131.473, and MAPE= 0.152%, and Trend Moment MAD= 132.447, MSE= 17788.856, and MAPE= 2.261%. So, the chosen method is Exponential Smoothing.